Water resilience for human prosperity - Rockstrom, Johan (New York : Cambridge University Press, 2014)
'The world's human population now constitutes the largest driving force of changes to the biosphere. Emerging water challenges require new ideas for governance and management of water resources in the context of rapid global change. This book presents a new approach to water resources, addressing global sustainability and focusing on socio-ecological resilience to changes. Topics covered include the risks of unexpected change, human impacts and dependence on global water, the prospects for feeding the world's population by 2050, and a pathway for the future. The book's innovative and integrated approach links green and blue freshwater with terrestrial and aquatic ecosystem functions and use. It also links changes arising from land-use alteration with the impacts of those changes on social-ecological systems and ecosystem services. This is an important, state-of-the-art resource for academic researchers and water resource professionals, and also a key reference for graduate students studying water resource governance and management'--
7. Water resources and functions for agro-ecological systems at the landscape scale Social-hydrological-ecological systems at the landscape scale -- Agricultural expansion and intensification affects landscape multifunctionality -- Three examples of landscape transformations and possible transitions -- Part IV. Governance and Pathways: -- 8. Governance for navigating the novel freshwater dynamics of the Anthropocene -- The Anthropocene era requires novel governance and management -- IWRM: the dominant paradigm -- Governance frontiers -- Signs of a paradigm shift and managing change -- Governance of transformation: a multi-level challenge -- 9. Pathways to the future -- Bloodstream management -- A new global water situation in the Anthropocene era -- The need to reconnect with the biosphere -- Towards'water stewardship for resilience'.
Includes bibliographical references and index.
Keywords: Water -- History; Water-supply -- History; Drinking water -- History